Depression Tendency in Students - Allda Manoeain; Serlie K. A. Littik; Dian Lestari Anakaka (Universitas Nusa Cendana, 2022)
WHO states that many mental health problems arise in late childhood and early adolescence because this period is full of physical and mental changes before reaching adulthood so adolescents have to adapt to many things that if they cannot handle the existing problems, can lead to disappointment and frustration. a sense of failure and susceptibility to mental disorders, one of which is depression. Depression is the third largest psychological disorder which is estimated to occur in 5% of the world's population (WHO, 2013). In a month about 4-5 teenagers come to consult. Adolescents who came to consult with clinical psychologists ranged in age from 17-25 years with varied educational backgrounds, and the adolescents who consulted the most were aged 19-22 years. Most show symptoms of severe depression and self-harm to the point of almost committing suicide.